Desenvolvimento de uma bancada de teste de desgaste abrasivo para barras de trilha de colheitadeiras de grão : um comparativo de desempenho em aços SAE 1045 e SAE 1518 - Werner, Marcos (2013)
The objective of the present work is to develop a study of abrasive wear a specific component of a grain harvester, the bars of unit threshing the combines. For this study it was designed and built a test bench that simulates two types of materials, an ABNT/SAE 1045 steel and an ABNT/SAE 1518 steel underwent a forced to wear an abrasive that simulates the size and condition of a grain at a accelerated rate. This bench is in turn composed of parts used in systems threshing on harvesters in order to bring the test closer to the real. The general condition of the abrasive was compared with the literature in order to obtain better data with respect to wear on the condition. After the wear test was designed to better characterize this wear, where it is noted that medium carbon steel (SAE 1045) had a good initial performance with respect to wear, however the material with manganese (SAE 1518) showed a better resistance at the end of the tests when compared to SAE 1045. Finally, the tests was conducted to validate the bench, and characterization of abrasive wear in relation to which it was possible to sense the increased wear of the samples was performed when adding the SiO2 abrasive to simulate rice hull.